A escrita da História na trilogia da maldição: Cantares de um anjo maldito - Pereira, Nuno Gonçalves (2004)
This paper analyzes the relationship between memory and history, ethics and aesthetics, historiography and myth, in José Alvides Pinto 's Trilogy of the Curse. I seek to enter the labyrinthine universe of artistic creation by crossing the paths of biographical gestures of the works produced [...].